Chronic intermittent hypoxia enhances tau seeding and propagation and exacerbates Alzheimer's‐like memory and synaptic plasticity deficits and molecular signatures: Molecular and cell biology: Tau‐related mechanisms. (7th December 2020) - Kazim, Syed Faraz; Sharma, Abhijeet; Larson, Chloe S.; Ramakrishnan, Aarthi; Blitzer, Robert; Shen, Li; Pena, Catherine; Crary, John F.; Shimoda, Larissa; Nestler, Eric; Pereira, Ana C.
Abstract: Background: Obstructive sleep apnea (OSA), characterized by sleep fragmentation and chronic intermittent hypoxia (CIH), is a risk factor for Alzheimer's disease (AD) development and progression. Recent epidemiological studies point to CIH as the best predictor of developing cognitive decline and AD in elderly with OSA. However, the precise underlying mechanism(s) remain unknown. Tau pathology, a major neuropathological hallmark of the disease, is known to be correlated with cognitive impairment in AD. Further, increase in tau pathology has been linked to CIH suggesting that CIH may mediate AD risk through tau pathology. The present study was undertaken to evaluate the effect of CIH on human tau seeding and propagation, and to further investigate the effects of CIH on cognition, synaptic plasticity, neuronal network excitability, and gene expression profiles in a human mutant tau mouse model of AD and related tauopathies (P301S mice). Method: We exposed 4‐4.5‐month‐old, male, mutant human tau P301S/WT mice to an 8‐week CIH protocol simulating human OSA (6 m cycle: 21% O2 to 8% O2 to 21% O2, 80 cycles per 8 h during daytime), and assessed its effect on tau seeding and spread and on various AD‐related phenotypic and molecular signatures. Age‐ and gender‐ matched P301S/WT mice were reared in normoxia (21% O2 ) as experimental controls. Result: Experimentally induced CIH significantly enhanced human tau seeding and spread across connected neuroanatomical circuitry in the brains of a P301S mutant human tau model of AD; also, it increased phospho‐tau load in P301S mice. CIH also exacerbated memory deficit and synaptic plasticity impairment and increased disinhibition‐like behavior in P301S mice. However, CIH had no effect on seizure susceptibility and network hyperexcitability in these mice. Finally, CIH exacerbated AD‐related pathogenic molecular signaling in P301S mice. Conclusion: In a comprehensive panel of immunohistochemical, behavioral, biochemical, electrophysiological, and transcriptomic analyses, we found that CIH enhances human tau seeding and spread, and exacerbates tau pathology, cognitive deficit, disinhibition‐like behavior, short‐ and long‐term synaptic plasticity impairment, and AD‐related molecular signaling in P301S mouse model of AD and related tauopathies. These data provide a mechanistic basis of a role for CIH and OSA in AD pathogenesis.